Effectiveness of the Training on Improved Technology of Postharvest Handling of Mango: An Empirical Evidence From Chapainawabganj District of Bangladesh (Research in Agriculture Livestock and Fisheries, 2020)
The present study aims at examining the effectiveness of the training on “Application of Improved technology of postharvest handling of Mango”. The research was conducted in three upazilas of Chapainawabganj district- a leading mango growing region of Bangladesh. A total of 50 respondents were selected randomly from the list of the trainees taking 25 from each of the trader‟s and farmer‟s group. The data were collected from the selected respondents employing direct interview method using pre-designed, pre-tested interview schedule. Both descriptive and statistical analysis was used in analyzing the data. The findings of the study revealed that majority of the respondents (94%) were educated and belonged to young aged group of 23-40 years. The study showed that before receiving the training, the postharvest losses at farm and traders‟ level accounted for 28.12% and 21.80%, respectively and after receiving training, the postharvest losses reduced to 12.68% at farm and 8.52% at traders‟ level which was significant at 95% level of confidence. The findings also revealed that after obtaining training, income of respondents had increased significantly by 25.47% at farm and 16.48% at traders‟ level. The study identified important problems faced by the respondents such as lack of capital, costly and unavailability of BARI (Bangladesh Agricultural Research Institute) mango harvester and hot water treatment plant in the market and limited access to institutional credit. If these constraints were removed, postharvest losses of mango could be reduced substantially thus ensuring increased sustainable income for both mango cultivators and traders. A pool of master trainers should be developed to train a large number of mango cultivators and stakeholders on this important issue, government should provide institutional credit to the mango farmers and traders at an ease terms and condition, BARI mango harvester and hot water treatment plant should be made available at an affordable price to the farming community and traders in mango growing regions of BangladeshRes. Agric., Livest. Fish.7(3): 351-361,  December 2020